2008
DOI: 10.1177/1358863x07085517
|View full text |Cite
|
Sign up to set email alerts
|

Two exceptionally rare branching patterns of the aortic arch

Abstract: Magnetic resonance angiography of the thoracic aorta was performed in a 66-year-old man scheduled for a Bentall operation. Beside the known aneurysm of the ascending aorta, a rare variant branching sequence of the aortic arch was found (Panel A: view from posterior; R, right; ls, left subclavian artery; lv, left vertebral artery; lc, left common carotid artery; rv, right vertebral artery; rc, right common carotid artery; rs, right subclavian artery). Three-dimensional surface reconstructions depicted a common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The diagnosis of anomalies of thinner arteries that are several millimeters in diameter may also be possible depending on the techniques applied to interpret the CT images. The use of contrast medium definitely makes the diagnosis easier, as has been shown in previous reports (Palmer 1977; Rieger and Huber 1983; Chen et al 1998; Lemke et al 1999; Best and Bumpers 2002; Yanik et al 2004; Goray et al 2005; Akdeniz et al 2007; Ka-Tak et al 2007; Satti et al 2007; Kau et al 2008; Park et al 2008; Kim et al 2009; Matsuno et al 2009). …”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The diagnosis of anomalies of thinner arteries that are several millimeters in diameter may also be possible depending on the techniques applied to interpret the CT images. The use of contrast medium definitely makes the diagnosis easier, as has been shown in previous reports (Palmer 1977; Rieger and Huber 1983; Chen et al 1998; Lemke et al 1999; Best and Bumpers 2002; Yanik et al 2004; Goray et al 2005; Akdeniz et al 2007; Ka-Tak et al 2007; Satti et al 2007; Kau et al 2008; Park et al 2008; Kim et al 2009; Matsuno et al 2009). …”
Section: Discussionmentioning
confidence: 61%
“…However, an anomalous origin of the right vertebral artery has been reported to be rarer, being detected as a coincidental finding during surgery or at autopsy (Akdeniz et al 2007). In fact, many of the reports describing anomalous origin of the right vertebral artery are coincidental findings during surgery (Palmer 1977; Rieger and Huber 1983; Chen et al 1998; Lemke et al 1999; Best and Bumpers 2002; Yanik et al 2004; Goray et al 2005; Akdeniz et al 2007; Ka-Tak et al 2007; Satti et al 2007; Kau et al 2008; Park et al 2008; Kim et al 2009), although such findings at autopsy have also been reported (Mori et al 1990; Gluncic et al 1999; Fazan et al 2004; Ikegami et al 2007). The same concomitant anomalies of the right subclavian artery and right vertebral artery as those observed in our study have been reported previously, although the vertebral artery enters the transverse foramen at various levels (Mori et al 1990; Gluncic et al 1999; Fazan et al 2004; Ka-Tak et al 2007; Kau et al 2008; Park et al 2008; Kim et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Origin of right vertebral artery from aorta distal to that of the left subclavian artery is very rare. Only 17 cases have been reported to date [1][2][3][4][5][6][7][8][9][10][11][12][13], including cases wherein both vertebral arteries arose from the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…El impacto de estas variaciones anatómicas es muy diverso ya que a pesar de pasar desapercibidos en la mayoría de los casos y convertirse en hallazgos incidentales de disección anatómica (Schwarzacher & Krammer, 1989), hay algunos reportes en los cuales son diagnosticadas al evaluar patologías cardiovasculares (Akdeniz et al, 2007;Paraskevas et al, 2008) respiratorias o digestivas asociadas (Kaus et al,. 2008;Szpinda, 2005) e incluso en cirugía de trauma con resultados no siempre favorables (Bustamante et al, 2007;Satyapal et al).…”
Section: Introductionunclassified